Molecular dynamics simulation of argon in solid?liquid phase transition region - Özgen, Soner; Kuzucu, Veysel; Adigüzel, Osman (My University, 1997)
The microstructure of 256 argon atoms located on ideal fee lattice sites on which periodic boundary conditions have been applied at the vicinity of transition temperature has been investigated. The forces among atoms have been derived from Lennard-Jones potential energy function and the equations of motion of the system have been solved by using the Verlet algorithm. The variations in microstructure have been investigated by means of radial distribution function and real-space atomic trajectories. It has been found from the results of simulation at zero pressure that solid-liquid transition temperature is 86K, the change of enthalpy is 1202 J/mol and relative volume change is 0.14. © Tübi?tak.